PENANAMAN NILAI-NILAI NASIONALISME MELALUI KEGIATAN PEMBIASAAN DIRI DI TAMAN KANAK KANAK KEMALA BHAYANGKARI 03 SELONG - Samsul Mujtahidin; Sry Anita Rachman (LPPM Institut Pendidikan Nusantara Global, 2021)
This research aimed at describing nationalism values inculcation through daily activities in Kindergarten Kemala Bhayangkari 03 Selong. It used qualitative approach by involving the headmaster and teacher as the participants. The data were collected by addressing observation, interview, and documentation techniques. These data were collected, reduced, presented, and concluded. Its validity was measured using sources and techniques triangulation. The findings showed that the inculcation of nationalism values was done through self-habitutation activities, such as; First, practicing marching activities, praying before and after the activities, having breakfast together, and doing gymnastics, religious activities, flag ceremony, and kids-police training. Second, exemplary behavior, such as; dressing, talking, and behaving. Third, spontaneous activities, namely; giving admonishment and direction.